Implementation of a nonlinear filter for online nuclear counting. (April 2016) - Coulon, R.; Dumazert, J.; Kondrasovs, V.; Normand, S.
Abstract: Nuclear counting is a challenging task for nuclear instrumentation because of the stochastic nature of radioactivity. Event counting has to be processed and filtered to determine a stable count rate value and perform variation monitoring of the measured event. An innovative approach for nuclear counting is presented in this study, improving response time and maintaining count rate stability. Some nonlinear filters providing a local maximum likelihood estimation of the signal have been recently developed, which have been tested and compared with conventional linear filters. A nonlinear filter thus developed shows significant performance in terms of response time and measurement precision. The filter also presents the specificity of easy embedment into digital signal processor (DSP) electronics based on field-programmable gate arrays (FPGA) or microcontrollers, compatible with real-time requirements. © 2001 Elsevier Science. All rights reserved. Highlights: An efficient approach based on nonlinear filtering has been implemented. The hypothesis test provides a local maximum likelihood estimation of the count rate. The filter ensures an optimal compromise between precision and response time.